[FULL RETRACTION] Common Grammatical Errors in Written Discourse of EFL Iraqi Learners - Al-shammery, Doaa Faris; Huesiani, Azar; Shahriari, Hesamoddin (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The current study was an attempt to explore the common grammatical errors in written discourse of EFL Iraqi learners across gender. To this end, five male and five female Iraqi EFL academic learners with the same proficiency level were randomly selected. The participants were supposed to write a descriptive composition on a common topic. Findings showed Iraqi EFL learners made various errors in the following categories including tenses, prepositions, articles, active and passive voice, verbs and morphological error. It has been found that most of these errors caused by the effect of grammatical and linguistic system of participants’ first language on their written production of the target language.